Late Pleistocene Oxygen-Isotope Records of Biogenic Silica from the Atlantic Sector of the Southern-Ocean - Shemesh, A.; Burckle, L. H.; Hays, J. D. (Paleoceanography, 1995)
We determined the isotopic composition of oxygen in marine diatoms in eight deepsea cores recovered from the Atlantic sector of the Southern Ocean. The analytical reproducibility and core-to-core consistency of the isotopic signal suggests that diatom delta(18)O can be used as a new paleocenographic tool to reconstruct past variations in surface water characteristics and to generate O-18 -isotope-based stratigraphy for the Southern Ocean. The data indicate that diatom delta(18)O reflects sea surface temperature and seawater isotopic composition and that diatoms retain their isotopic signal on timescales of a least 430 ka. The delta(18)O analyses of different diatom assemblages reveal that the isotopic signal is free of species effects and that the common Antarctic species have the same water-opal fractionation. The transition from the last glacial maximum (LGM) to the Holocene is fully recorded in high sedimentation rate cores. An O-18 enrichment during the LGM, a post-LGM meltwater spike and an input of meltwater during the late Holocene are the main isotopic features observed in down core records. The origin of this meltwater was very likely melting icebergs and/or continental ice or by melting sea ice that had accumulated snow. The most pronounced meltwater effects are recorded in cores that are associated with the Weddel gyre. Our results provide the basis for extending isotope studies to oceanic regions devoid of carbonate; further, isotopic stratigraphies may be constructed for records and regions where they were previously not possible.
Rd382Times Cited:82Cited References Count:23